تأثير استخدام استراتيجيات التسعير على رضا العميل في مؤسسات القطاع العام في سورية: دراسة ميدانية على عملاء المؤسسة السورية للتجارة - شيخ ديب، صلاح محمد; معلا، ريهام حسين; السكري، أحمد (جامعة تشرين, 2022)
هدف البحث إلى التعرف على العلاقة بين استخدام الاستراتيجيات التسعيرية وتعزيز رضا العميل في المؤسسة السورية للتجارة، من خلال تحديد مدى تأثير كل من أبعاد الاستراتيجيات التسعيرية والمتطلبات الأساسية لتطبيقها على رضا العميل، وقد اعتمدت الباحثة على المقاربة الاستنباطية وعلى المنهج الوصفي كمنهج عام للبحث، وقامت بتوزيع استبيان على (384) فردا على العملاء المتعاملين مع المؤسسة السورية للتجارة الوسط الحسابي والمتوسط، وقد خلصت هذه الدراسة إلى عدة نتائج، كان أهمها وجود علاقة مباشرة بين استخدام الاستراتيجيات التسعيرية ورضا العميل، وهذه العلاقة مقبولة وموجبة، ويعود السبب في ذلك إلى ضعف وجود مهارات موارد بشرية ووجود برنامج أسعار غير مناسب، كما قدمت العديد من المقترحات والتوصيات، والتي كان أهمها ضرورة وضع استراتيجية مناسبة لاستخدام الاستراتيجيات التسويقية الداعمة لعملياتها في إطار الاستراتيجية العامة للمؤسسة، ومتابعة تنفيذها وتقييمها بما يحقق الأهداف الأساسية للمؤسسة. The research aimed to identifying the relationship between the use of pricing strategies and enhance of customer satisfaction in Study in the Syrian trading corporation. By identifying the extent of the impact of each dimensions of pricing strategies, by determining the extent to which both the pricing strategies dimensions and the basic requirements of the application of pricing strategies affect customer satisfaction, the researcher relied on the prescriptive approach and the descriptive approach as a general approach to research, the questionnaire was distributed to 384 person from customer in the Syrian trading corporation like Mean, and this study concluded several results, the most important of which was a moral relationship between the use of pricing strategies and the customer satisfaction, and this relationship is acceptable and positive, and is due to the lack of human resource skills and an inappropriate price programme, the researchers have reviewed many important results and made several suggestions and recommendations, the most important of which was the need to develop an appropriate strategy for the use of pricing strategies supporting its operations within the overall strategy of the organization and following up on its implementation and evaluation in order to achieve the basic objectives of the organization.
Keywords: منظمات الأعمال -- إدارة التسويق -- التخطيط الاستراتيجي -- رضا العملاء -- القطاع العام -- سوريا